Between Spirituality and Social Context: Unpacking ‘Kidung Rumekso Ing Wengi’ in Javanese Society - Khusniyah, Aziizatul; Cahyandari, Rinova (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This study aims to understand how "Kidung Rumekso Ing Wengi" influences the social dynamics and identity of Javanese society, as well as how the chant adapts to and affects social and cultural changes. The method used in this study is qualitative with a library research approach. Through the analysis of relevant ancient literature, this article provides a deep understanding of the cultural background of "Kidung Rumekso Ing Wengi" and its impact on contemporary Javanese society. The results show that "Kidung Rumekso Ing Wengi" brings peace and protection and strengthens Javanese cultural identity in the face of the modern world. The adaptation and cultural resilience of the "Kidung Rumekso Ing Wengi" practice demonstrate the flexibility and dynamism of Javanese traditions and their role in fostering communal ties. This research enhances the understanding of how deeply rooted spiritual traditions shape social life and offers important insights into the importance of maintaining and understanding cultural practices in the face of contemporary challenges.